Job crafting and innovative behavior among hospitality workers: The moderation effect of work engagement - Kaur, Gursweet; Rahmadani, Vivi Gusrini (HUMANITAS published by Universitas Ahmad Dahlan., 2023)
The COVID-19 pandemic impacted a decline in hotel occupancy rates in the hospitality sector worldwide, including in Indonesia. Therefore, hotel management and workers need innovation to attract customers by crafting their jobs and developing original and creative ideas. Moreover, employees’ work engagement will also support the emergence of innovative behavior. This study aimed to explore whether work engagement moderates the relationship between job crafting and innovative work behavior among hotel employees. This research was conducted at one of the four-star hotels in Medan, with 109 employees chosen with a total sampling technique to participate in this study. The innovative behavior scale, the job crafting scale, and the work engagement scale were used to collect the data, which were then processed using the moderated regression analysis method with Process Macro Software. The results show job crafting has a significant positive effect on innovative behavior, and work engagement moderates the effect of job crafting on innovative behavior. Increasing innovative behavior can be achieved by increasing job crafting and work engagement in the organization. The implication of this study may assist the hotel management in assessing its employees and then implementing training on job crafting and work engagement to improve innovative behavior.